Science and Societal Partnerships to Address Cumulative Impacts - Lundquist, Carolyn J.; Fisher, Karen T.; Le Heron, Richard; Lewis, Nick I.; Ellis, Joanne I.; Hewitt, Judi E.; Greenaway, Alison J.; Cartner, Katie J.; Burgess-Jones, Tracey C.; Schiel, David R.; Thrush, Simon F. (Frontiers in Marine Science, 2016)
Funding and priorities for ocean research are not separate from the underlying sociological, economic, and political landscapes that determine values attributed to ecological systems. Here we present a variation on science prioritisation exercises, focussing on inter-disciplinary research questions with the objective of shifting broad scale management practices to better address cumulative impacts and multiple users. Marine scientists in New Zealand from a broad range of scientific and social-scientific backgrounds ranked 48 statements of research priorities. At a follow up workshop, participants discussed five over-arching themes based on survey results. These themes were used to develop mechanisms to increase the relevance and efficiency of scientific research while acknowledging socio-economic and political drivers of research agendas in New Zealand’s ocean ecosystems. Overarching messages included the need to: 1) determine the conditions under which ‘surprises’ (sudden and substantive undesirable changes) are likely to occur and the socio-ecological implications of such changes; 2) develop methodologies to reveal the complex and cumulative effects of change in marine systems, and their implications for resource use, stewardship, and restoration; 3) assess potential solutions to management issues that balance long-term and short-term benefits and encompass societal engagement in decision-making; 4) establish effective and appropriately resourced institutional networks to foster collaborative, solution-focused marine science; and 5) establish cross-disciplinary dialogues to translate diverse scientific and social-scientific knowledge into innovative regulatory, social and economic practice. In the face of multiple uses and cumulative stressors, ocean management frameworks must be adapted to build a collaborative framework across science, governance and society that can help stakeholders navigate uncertainties and socio-ecological surprises.